Factors critical for the success of public‒private partnerships in UAE infrastructure projects: experts' perception. Issue 3 (2nd July 2016) - Al-Saadi, Rauda; Abdou, Alaa
Abstract : During the last decade, the United Arab Emirates (UAE) has been the biggest market for public–private partnerships (PPPs) in Gulf Cooperation Council (GCC) countries. Currently, PPPs are increasingly being used in the rapid development of UAE infrastructure projects. Despite this fact, little is known about the success factors for adopting such an approach for the infrastructure projects in the UAE. Twenty-one in-depth interviews were held with PPP experts and key personnel who have experience in the development life cycle of PPP infrastructure projects in the UAE in order to investigate their perception of the key success factors of PPP in UAE infrastructure projects and examine the relative importance of these factors. The results show that the five most important critical success factors (CSFs) for all respondents were: availability and effectiveness of proper regulatory and legal framework for PPPs; proper risk allocation and sharing among project stakeholders; clear project brief and client outcomes; comprehensive and business viability of project feasibility study; and finally, proper project value management systems during different project phases. These findings should be taken into consideration by public and private partners when developing new PPP projects in the UAE in order to increase the success rates of these projects.